Thermal Analysis, Phase and Morphological TransformationS in the Composites Aluminosilicate Nanotubes/Acetates of Ni, Cu, Zn - O. I. Oranska; Yu. I. Gornikov; A. V. Brichka; S. Ya. Brichka (Хімія, фізика та технологія поверхні)
The thermal stability and solid-phase reactions in composites halloysite nanotubes – acetates of Ni, Cu, Zn in the temperature range from 20 to 1100°C have been investigated. It has been shown that chemical reactions occur with metal oxides formed due to thermal degradation of acetates and components of aluminosilicate matrix formed during dehydration and dehydroxylation of halloysite nanotubes. Reaction products are nanocrystalline ZnAl2O4 distributed in a matrix of amorphous SiO2 and CuO solid solution in ?-cristobalite. Degree of destruction of the tubular structure of nanotubes in the composites with acetate increases as follows: Ni2+ < Zn2+ < Cu2+.